2009
DOI: 10.1007/s00330-009-1614-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of gallbladder problems using three-dimensional ultrasound

Abstract: This study shows that 3DUS diagnosis correlates well with 2DUS with regard to most gallbladder problems and could be sufficient as a stand-alone technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…These images can be reviewed by a cardiologist to determine significance before referral to a radiologist trained in the evaluation of gallstones and gallbladder pathology. Preliminary studies have shown that 2DU and 3DU have similar sensitivity and specificity in diagnosing common gallbladder pathology 7,8 but to our knowledge, no studies have evaluated Although none of the patients presented with cholecystitis, one patient had gallbladder wall thickening on 2DE and all three on 3DE. In patient 2, Figure 4AB revealed marked thickening of the gallbladder wall after cropping of the 3D data set in the posterior-anterior direction.…”
Section: Discussionmentioning
confidence: 94%
“…These images can be reviewed by a cardiologist to determine significance before referral to a radiologist trained in the evaluation of gallstones and gallbladder pathology. Preliminary studies have shown that 2DU and 3DU have similar sensitivity and specificity in diagnosing common gallbladder pathology 7,8 but to our knowledge, no studies have evaluated Although none of the patients presented with cholecystitis, one patient had gallbladder wall thickening on 2DE and all three on 3DE. In patient 2, Figure 4AB revealed marked thickening of the gallbladder wall after cropping of the 3D data set in the posterior-anterior direction.…”
Section: Discussionmentioning
confidence: 94%
“…[17] Three-dimensional ultrasonography Three-dimensional ultrasound (3DUS) diagnosis correlates well with two-dimensional ultrasound (2DUS) with regard to most gallbladder problems and could be sufficient as a stand-alone technique. [18] …”
Section: Ultrasonographymentioning
confidence: 99%
“…It was presented a small case series of patients with gallbladder polyps that were correctly diagnosed preoperatively as benign or malignant with the use of positron emission tomography scanning with 18 F-labelled deoxyglucose. [8] …”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…Although the increased accuracy of the assessment of renal perfusion is known to be increased using CEUS, the clinical relevance of these tiny perfusion defects is currently not known, although it has been suggested that they may be a cause for patients with "stuck" creatinine [12]. The aim of this study, therefore, was to assess the prevalence and size of perfusion defects in renal transplantation patients following surgery using 3D CEUS in an attempt to determine the significance of these perfusion defects on renal function.…”
Section: Introductionmentioning
confidence: 99%